COMPARISON OF DIFFERENT COMMERCIAL SEROLOGY KITS FOR THE DETERMINATION OF SEROPOSITIVE TOXOPLASMOSIS IN CATTLE IN INDONESIA - Didik T Subekti; Sisca Valinata; Sulinawati Fong (Jurnal Kedokteran Hewan, 2021)
This research aims to explain the evaluation of the differences in four commercial kits for the detection of serological toxoplasmosis used in Indonesia.  The results of the study found that the toxoplasmosis seropositivity determined by the four commercial kits showed a significant difference (P0.05).  Seropositive toxoplasmosis obtained using Pastorex, Toxotest, IDScreen, and Toxo Ab were 35.12%, 60.12%, 26.19%, and 10.12% respectively.  IDScreen had a good agreement with Toxo Ab (Gwet's AC1= 0.623) and a moderate agreement with Pastorex (Gwet's AC1= 0.494-0.511).  Toxotest had a low agreement with three commercial kits (Gwet's AC1= 0.2) but had a moderate agreement with western blotting (WB) and modified agglutination test (MAT) (Gwet's AC1= 0.458-0.557).